A produção de si pelo trabalho : estratégias, práticas e experiências juvenis - Benevides, Márcio Renato Teixeira (2019)
This research is based on an ethnobiographic analysis of the stories of five young people from Ceará who live from their own work. In this way, the objective was to find interpretations of these interlocutors about labour and how their understandings make sense to constitute them as individuals. In activities marked by the need to deal with difficulties, carrying themselves well, these young people acted in order to inscribe their own meanings in their trajectories through what they do. In very different situations, such as the boy who has become a YouTube personality or one who has worked for a decade in the same outsourced company, it is possible to understand the effects of work on their lives. Even in situations where "overload", "pain" and "pressure" are constructed, it is also possible to find intentions based on "creativity", "desire", "innovation" and "art", demonstrating that there is a positive economy and that individuals resist in some way, bringing an action against the structures. Contexts can be tough, but this does not mean that the so-called vocations and intentions about a better future are necessarily eliminated. It is worth mentioning that a number of interviews were conducted, in addition to a series of moments shared between interlocutors and researcher, so that we could reach the material to elaborate this thesis.